Kewenangan Dinas Kehutanan Dalam Menanggulangi Tindak Pidana Illegal Logging (Studi Penelitian Dinas kehutanan Kabupaten Pakpak Bharat) - Tumangger, Silfia; A, Arnita; Iskandar, Hadi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to examine the authority, obstacles and efforts made by the Forestry Service in tackling the crime of Illegal Logging in Pakpak Bharat Regency. This research uses empirical legal research with a sociological juridical approach. Based on the research results, it is known that the authority of the forestry service in dealing with illegal logging crimes in the Pakpak Bharat district begins with reports, inspections by forest police and the forestry service. Patrol every forest that has experienced damage, but the implementation is not yet optimal because there are several obstacles or barriers to the implementation of tackling the criminal act of illegal logging, which is related to the lack of public awareness about the importance of forests and the impact of these activities, forestry officers and forest police are very minimal. Lack of supporting facilities to patrol to tackle illegal logging crimes in Pakpak Bharat Regency.